HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT MURID SEKOLAH DASAR - Aida Silfia; Slamet Riyadi; Pahrur Razi (Jurnal Kesehatan Gigi, 2019)
One of the causes of oral problems is the oral hygiene neglect. Despite the high knowledge in oral health care, lot of children still unable to improve their attitude and practice towards oral health care. The aim of this study is to define the association of knowledge level with behaviour towards oral health care in students of SDN 36/IV Jambi in 2018. This is a cross sectional study comprised of 59 subjects recruited by total sampling method. Data collected from questionnaire filled by subjects followed by chi square analysis. The high, moderate and low knowledge level of SDN 36/IV Jambi students were 66,1%, 32,2% and 1,7% respectively. 67,8% subjects had good behaviour towards oral health care, while the other 32,2% had moderate behaviour. No significant association found between knowledge level and behaviour towards oral health care in students of SDN 36/IV Jambi in 2018 (sig=0,446; p ˂ 0,05).